Discordant inflammation and pain in early and established rheumatoid arthritis: Latent Class Analysis of Early Rheumatoid Arthritis Network and British Society for Rheumatology Biologics Register data - McWilliams, Daniel F.; Ferguson, Eamonn; Young, Adam; Kiely, Patrick D.W.; Walsh, David A. (BioMed Central, 2016)
Background Rheumatoid arthritis (RA) disease activity is often measured using the 28 joint Disease Activity Score (DAS28). We aimed to identify and independently verify subgroups of people with RA that may be discordant with respect to self-reported and objective disease state, with potentially different clinical needs.